Innovative space-saving furniture for interior spaces - Angeles, Ma. Encarnacion Veluz
Statement of the Problem: Maximum space utilization through innovative furniture gadgetry. Methodology: Scope and Limitations: A specific area will be chosen for experimentation. In this case, it will be an apartment located in a rural area. The spatial requirements will be answered through the use of innovative space-saving furniture. Description of Subjects: The apartment chosen is a 4.0 x 9.0 M space located at the 2nd floor, AVM Building , Dasmarinas, Cavite. It is 3.0 M in height and facilities include a kitchen, toilet and bath area, and balcony. At present, the apartment is still unoccupied. Sampling: Surveys and questionnaires will be given out to students renting apartments in the AVM Building vicinity. Criteria is as follows: age-21 to 29, gender-male, income bracket-middle/upper class, course-Medicine Proper. Description of Instruments: Interviews, surveys, questionnaires, photo criticism method, and observation sheet. Gathering Data: June 1994 to May 1995. Treatment of Data: Tables, graphs, charts, diagrams will be used in the tabulation of results and will aid in the analysis. Results: From the study of the experimental area and the assistance of twenty sampling volunteers, the needs of the future occupants would be: and efficient study area, entertaining area, sleeping area, storage space, and diminished noise. These are the top problems of the sampling volunteers. The analysis of the problem and data produced a proposed floor plan with space-saving furniture designs.